The Effect Of Rewards On Employee Performance Through Punishment At Miss Cimory Center Purbaratu Tasikmalaya : - Fauzen, Dede Hanif; Rahwana, Kusuma Agdhi; Risana, Dudu (Jurnal Pakar Manajemen, 2025)
This research aims to find out how employees respond regarding the influence of reward and punishment at the Miss Cimory Center Purbaratu Tasikmalaya marketing department. The research method used was a survey method, data was obtained directly through questionnaires to 30 respondents taken from marketing department employees. Sampling used a census and the analysis method used in this research was path analysis. Based on the research results, the results show that rewards are classified as very good, punishment is included in the very good classification, and the performance of marketing employees is classified as good. Based on this research, there is a significant influence between reward and punishment on the performance of marketing employees.